Effects of Sexual Behaviour, Intercourse, Satisfaction-Related Myths and Perceived Spirituality on Sexual Dysfunctions in Muslim Pregnant Women - Uludağ, Elif (Journal of religion and health, 2021)
The aim of this study was to examine the effects of sexual behaviour, intercourse, satisfaction-related myths and spirituality on sexual dysfunctions in Muslim pregnant women. The study had a descriptive, cross-sectional and correlational design and was performed with 215 Muslim pregnant women. Descriptive statistics and multiple regression analyses were utilized for data analysis. As a result of the multiple regression analyses, sexual dysfunctions were most affected by sexual behaviour myths and least affected by perceived spirituality. It can be suggested that sexuality should be incorporated into prenatal care and counselling.